Vigil in Benicarló - Azaña, Manuel (Fairleigh Dickinson University Press, 1982)
Keywords: Civil War, 1936-1939; Drama; History; Spain; dept.his; faculty_collection

Hmong and Yao: Mountain Peoples of Southeast Asia - Hamilton-Merritt, Jane (SURVIVE, 1982)
Keywords: Hmong (Asian people); Yao (Southeast Asian people); Chemical warfare; award_winner; dept.his; faculty_collection

My First Days of School - Hamilton-Merritt, Jane (Simon & Schuster, 1982)
Five-year-old Kate relates the experiences of her first day in kindergarten.
Keywords: dept.his; faculty_collection

Our New Baby - Hamilton-Merritt, Jane (J. Messner, 1982)
Follows the experiences and changing feelings of a child during a year when a new baby becomes a part of his family.
Keywords: Infants; Juvenile literature; Juvenile literature; Parent and child; Juvenile literature; Siblings; dept.his; faculty_collection

Western religious thought - Ausmus, Harry J (Journal of the American Academy of Religion, 1982)
Keywords: dept.his

Review of Transcendentalism as a Social Movement, 1830-1850 - Caruthers, J. Wade (The American Historical Review, 1982)
Keywords: dept.his

Nuclear-weapons and the future - an unthinkable proposal - Tyler, RL (Humanist, 1982)
Keywords: dept.his; ⛔ No DOI found